Gabon : Increasing Economic Diversification and Equalizing Opportunity to Accelerate Poverty Reduction - World Bank Group (World Bank, Washington, DC, 2020)
This Systematic Country Diagnostic (SCD) analyzes the economic and social context of Gabon and what it can do today to end extreme poverty and enhance shared prosperity. It also identifies priority routes to faster progress. Two critical pathways to sustained inclusive growth and shared prosperity have been identified in this SCD: • Economic diversification is crucial to revamp growth, increase productivity, and build resilience to volatility in commodity markets. • Equalizing opportunities and enhancing human capabilities can broaden access for all Gabonese to public services and better job opportunities and build productivity, competitiveness, and inclusive growth.